2006
DOI: 10.2139/ssrn.900521
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Strategic Use of Corporate Social Responsibility

Abstract: We thank Joshua Intriligator and Jennifer Silverstein for capable research assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
355
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(374 citation statements)
references
References 26 publications
12
355
0
7
Order By: Relevance
“…These findings can be viewed as a theoretical support for the empirical judgment of Fabrizio [12] that voluntary CSR disclosure can be interpreted as a signal of product quality, and the empirical observation of [13] that firms selling experience goods and credence goods are more likely to be socially responsible than firms selling search goods. Moreover, we show in Proposition 2 that the high-quality supplier gets a higher profit than the low-quality supplier if the former conducts CSR activities to separate from the latter.…”
Section: Discussionsupporting
confidence: 63%
“…These findings can be viewed as a theoretical support for the empirical judgment of Fabrizio [12] that voluntary CSR disclosure can be interpreted as a signal of product quality, and the empirical observation of [13] that firms selling experience goods and credence goods are more likely to be socially responsible than firms selling search goods. Moreover, we show in Proposition 2 that the high-quality supplier gets a higher profit than the low-quality supplier if the former conducts CSR activities to separate from the latter.…”
Section: Discussionsupporting
confidence: 63%
“…The authors showed that the difference in the intensity of CSR involvement across types of goods is explained by the consumers' perception of a firm's involvement in CSR as a valuable signal of the firm's reliability and its commitment to quality and honesty. In this regard, the research findings state that a positive impact of CSR on performance is generally found in consumer industries and especially for experience goods and credence services (Baron et al, 2009;Hoepner et al, 2010;Siegel and Vitaliano, 2007). Previous research supports this assumption (e.g., Calabrese and Lancioni, 2008;García de los Salmones et al, 2005;Maignan and Ferrell, 2001;Sureshchandar et al, 2001Sureshchandar et al, , 2002.…”
Section: Csr Effect On Performance In Service Firms Vs Goods Firmsmentioning
confidence: 88%
“…Customers often use corporate reputation to assess products, with positive reputation resulting in higher perceptions of product/service quality (Jacoby et al, 1971;Shapiro, 1982). In the minds of some consumers, CSR is a signal of honesty and reliability, and a reliable and honest firm is believed to produce better products (Siegel and Vitaliano, 2007). Siegel and Vitaliano (2007) found that firms selling experience goods (i.e., products whose characteristics cannot be verified before buying or using them), and experience and credence services are more likely to engage in CSR than those selling search goods (i.e., products whose characteristics can be identified before buying).…”
Section: Csr Effect On Performance In Service Firms Vs Goods Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increased CSR awareness among Malaysian companies and noteworthy efforts to go beyond the standard industry and Bursa Malaysia reporting requirements, the quality of CSR disclosures within Malaysian annual reports is dismal to the normal scope of corporate financial reporting (MaSRA, 2013). Previous studies have suggested the importance of company-specific characteristics as proxies in inducing their disposition and responsiveness in disclosing additional CSR information voluntarily (Lan et al, 2013;Gamerschlag et al, 2011;Siegel and Vitaliano, 2007;Orlitzky et al, 2003). Thus, this study seeks to determine the pre-existing influence of company-level variables on the level of sustainability reporting preceding the transitional implementation period of the G4 Sustainability Reporting Guidelines in 2014 and 2015. In addressing the internal organisational factors of sustainability reporting, extensive literature search indicated dearth of quantified measures on board experience as an antecedent to CSR disclosure levels.…”
Section: Literature Reviewmentioning
confidence: 98%